Bone Marrow Recovery and Subsequent Chemotherapy Following Radiolabeled Anti-Prostate-Specific Membrane Antigen Monoclonal Antibody J591 in Men with Metastatic Castration-Resistant Prostate Cancer - Tagawa, Scott T.; Akhtar, Naveed H.; Nikolopoulou, Anastasia; Kaur, Gurveen; Robinson, Brian; Kahn, Renee; Vallabhajosula, Shankar; Goldsmith, Stanley J.; Nanus, David M.; Bander, Neil H. (Frontiers in Oncology, 2013)
Radioimmunotherapy has demonstrated efficacy with acceptable toxicity leading to approval in non-Hodgkin’s lymphoma, but has been slower to develop for the treatment of advanced solid tumors. Prostate cancer represents a good candidate for radioimmunotherapy based upon high exposure to circulating antibodies at common disease sites with a specific, highly expressed cell-surface antigen in prostate-specific membrane antigen. Four phase I and II trials utilizing 177Lu- or 90Y-J591 have been reported. Long-term toxicity and chemotherapy administration was analyzed. As expected, the only serious toxicity observed was myelosuppression. Grade 4 thrombocytopenia occurred in 33.3% without significant hemorrhage and grade 4 neutropenia occurred in 17.3% with 0.07% febrile neutropenia. Nearly all subjects (97.3%) recovered to grade 0 or 1 platelets and all had complete neutrophil recovery. The majority (81.3%) received chemotherapy at any time, with 61.3% receiving chemotherapy following radioimmunotherapy. Ten subjects underwent bone marrow biopsies at some point in their disease course following radioimmunotherapy for low counts; all had diffuse prostate cancer infiltration without evidence of myelodysplasia or leukemia. As expected, myelosuppression occurs following therapeutic doses of radioimmunotherapy for men with metastatic castration-resistant prostate cancer. However, toxicity is predictable and self-limited, with the majority of patients who do not refuse able to receive cytotoxic chemotherapy following radioimmunotherapy.